2006
DOI: 10.1148/radiol.2402050807
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Local Efficacy and Survival after Radiofrequency Ablation of Lung Tumors with Minimum Follow-up of 1 Year: Prospective Evaluation

Abstract: RF ablation has a high local efficacy and is well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
3
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(155 citation statements)
references
References 21 publications
7
141
3
4
Order By: Relevance
“…(17). Despite a possible transient decrease during the first 3 weeks after ablation, the overall respiratory function tested at 3, 6 or 12 months after the intervention shows no degradation (25,41,42,47). …”
Section: Complicationsmentioning
confidence: 88%
See 3 more Smart Citations
“…(17). Despite a possible transient decrease during the first 3 weeks after ablation, the overall respiratory function tested at 3, 6 or 12 months after the intervention shows no degradation (25,41,42,47). …”
Section: Complicationsmentioning
confidence: 88%
“…Studies have reported more than 80% of treatment failure when the rim of ground-glass was not identified on control CT (39,40). When the total area of the thermal injury is four times that of the tumor, the success rate of complete necrosis is 96% whereas it falls to 80% if this proportion is not reached (41). Similarly, when the ablation volume is more than three times the tumor volume, tumor destruction is complete in 83% against 61% when this proportion is not reached (27).…”
Section: Lasermentioning
confidence: 99%
See 2 more Smart Citations
“…24 Ninety-seven of 100 targeted tumors were treated and showed an overall survival rate at 71% and a lung disease-free survival at 18 months of 34%. 24 At 18 months, the overall survival rates were 76% for primary lung tumors and 71% for metastatic disease. This study also reports a 54% rate of pneumothorax, with chest tube placement in 9% of the procedures.…”
Section: Outcomes and Comparison Of Thermal Ablation Techniquesmentioning
confidence: 99%